Eschatological Folk Songs and Poetry in the Manuscript Tradition of the Russian Old Believers of Latgale - Filosofova, Tatiana (FOLKLORICA - Journal of the Slavic, East European, and Eurasian Folklore Association, 2014)
Eschatological beliefs and teachings form the core of the RussianOld Believer theological doctrine and world view and are broadlyreflected in their writings and oral literature. This article sets out toexamine the particularities of the body of the eschatological folksongs and poetry known to the Russian Old Believers who live inthe eastern part of contemporary Latvia (Latgalia). The LatgalianOld Believer community is considered one of the richest, wellpreserved and fully functional communities of the bespopovtsy (the"priestless") branch in Europe today. This current research wasbased on material from the manuscript collections held in theDrevlekhranilishche IRLI (St. Petersburg, Russia) and field workcarried out in the Latgalian community between 2007 and 2010.First, the article describes the repertoire of eschatological songsand poetry that form the core of the written anthologies widelycirculated in the Latgalian tradition. It then moves on to analyzehow the eschatological teachings were interpreted in folk songsand poetry. Specifically, the research focuses on the folkinterpretation of the timing of the end of the world, the figure ofthe Antichrist and his realm. Finally, the article examines somelinguistic particularities of the religious songs and poetry and howthey were completed, edited and recorded in the Old Believermanuscripts.